The Influence of Motivation, Leadership, and Work Discipline on Employee Performance at PT. Suzuki Finance Indonesia - Deny Christiawan Simanjuntak; Jaymie Lawrence; Astono Wijaya; Jurisman Simanjorang (Journal of Research in Business, Economics, and Education, 2022)
PT. Suzuki Finance Indonesia is a joint venture company between ITOCHU Corporation and Suzuki Motor Corporation Japan and has been operating since May 2005. The purpose of establishing this company is to provide complete and best service to everyone who wants to get Suzuki motorized vehicles on credit easily. and safe. The results of this study can be seen that the partial hypothesis test obtained the value of the results of the calculation of motivation to obtain |3.014| > ttable > |0.214| and sig 0.04 < 0.05, the value of leadership results |-1.411| > ttable |0.214| and sig, 0.163 > 0.05, the result value of discipline |1.359| > ttable |0.214| and a sig of 0.179 <0.05 and the simultaneous result value Fcount (6.141) > Ftable (2.91) and a sig probability of 0.001 <0.05. The conclusion of this study is that the influence of motivation, leadership, and work discipline simultaneously and partially has a positive and significant effect on the performance of employees of PT. Suzuki Finance Indonesia.